AN ANALYSIS OF STELLA'S AND WILL'S LOVE LANGUAGE AND FREUDIAN TRIPARTITE IN in “FIVE FEET APART” FILM - Mulyadi, Mulyadi (TONIL: Jurnal Kajian Sastra, Teater dan Sinema, 2024)
The phenomenon that leads to the creation of this research is the implementation of love language in the “Five Feet Apart” film, and the inner workings of the three Freudian elements of the mind through the implementation of love language. This research has the objective toanalyzethe Freudian Tripartite using the framework of love languages, aiming to comprehend the personalities of characters in the film "Five Feet Apart" and unveil the relationship between the Freudian Tripartite and love languages through an analysis of their dialogues and behavior's. This research employs qualitative method with a descriptive framework, in which the object of study is the film itself. The observational and non-participatory technique isutilized tocollect the data, with the researcher acting as the instrument of the research. Qualitative data analysis employs the identity referential technique, focusing on utterances spoken by characters, namely Stella and Will. The analysis of findings reveals a substantial correlation between the three components of the Freudian Tripartite and the five love languages. This research unveils the interconnection between the expression and reception of love with psychological elements, emphasizing the influence of the mind on the behaviorsdemonstrated by characters such as Stella and Will in their expressions of love. Consequently, this study contributes to a novel comprehension of how psychological factors affect the act of expressing love within human relationships. By interpreting the correlation between Freudian Tripartite components and the five love languages, the research sheds light on the connection of psychological dimensions in the view of affectionate behaviors.